Spatial and Temporal Changes and Assessment of Multi-Species Habitat in Hainan Jianfengling Protected Area - Yong Ma; Lixi Liu; Wutao Yao; Zhigao Zeng; Mingjun Zhang; Erping Shang; Shuyan Zhang; Jing Yang (Remote Sensing)
The loss and fragmentation of wildlife habitats is a major threat to their survival and expansion, and protected areas (PAs) are the main tool for conserving biodiversity and protecting habitats. However, most current studies focus on analyzing suitable habitats for species and rarely analyze the spatial and temporal changes in multi-species habitats in protected areas and the effectiveness of conservation. In this study, we analyzed changes in the suitable habitats of five focal mammal species before and after the incorporation of the Hainan Jianfengling protected area into China’s national parks. We utilized the ensemble species distribution model (ESDM) to assess these changes, based on multi-species infrared camera monitoring data from 2015 to 2016 and 2020 to 2021. Furthermore, we evaluated differences in conservation effectiveness before and after the establishment of the national parks. The results showed that there were some differences in habitat changes among all the species included in this study, and all of them showed the phenomenon of the migration from suitable habitats to the central area. The environmental changes in and around the protected area suggest that the changes are closely related to the increase in anthropogenic activities around the protected area, and it is recommended that the protected area should be better managed at its edges to minimize the impact of anthropogenic disturbances on the species and their habitats.